Responsibility to Protect and the Challenges of Displaced Men in Nigeria: Array - Oghuvbu, Ejiroghene Augustine; Okolie, Ugo Chuks (Journal of Danubian Studies and Research, 2020)
This study addresses responsibility to protect and the challenges of displaced men in Nigeria. It argues that the challenges facing displaced people in Nigeria as a result of Boko Haram, natural and man-made disasters, as well as the Hausa-Fulani Mayhem are peculiar to all the IDPs irrespective of demographic disparities. It employs the use of qualitative and quantitative research methods drawing data from primary and secondary sources. Administering 256 questionnaires to men within the IDPs camp accompany with well structured interviews and focus group discussions with displaced men in Durumi Area 1 IDP camp Abuja. Secondary sources of data reviews existing literature from journals, online articles, and research projects. Findings show that the challenges of the men population ranging from starvation, water, hunger, electricity, accommodation shortages and lack of sustainable occupation foretell serious human security threats for the country. The study proposes relevant policies for government and other related agencies working with the IDPs; while, concluding that government should collaborate with individuals and organizations in providing vocational skills, that will help alleviate their plights.